(untitled) (Cardiovascular Journal, 2017)
Background: Contrast induced nephropathy (CIN) is not an uncommon complication of percutaneous coronary intervention (PCI) and it is more in diabetic patients. But we do not know the incidence and consequences of CIN of patients with high blood sugar but not known diabetic. We planned to find the relationship between level of admission blood glucose and contrast induced nephropathy after PCI in Acute Coronary Syndrome (ACS) in non-diabetic patients. Methods: This prospective observational study was conducted in National Institute of Cardiovascular Diseases, Dhaka from January 2012 to June 2012. Total 120 patients were observed in two groups, group-I non-diabetic with normal blood glucose (?7.8 mmol/L) and group-II non-diabetic with high blood glucose (?7.8 mmol/L). Results: Results show increase in serum creatinine (0.1mg/dl vs. 0.3 mg/dl) and decrease in creatinine clearance rate (12.9 ml/min vs. 6.0ml/min) was more in hyperglycemic than normoglycemic. When most common definition of contrast induced nephropathy was used, the incidence of CIN was 24% in high blood glucose group and 4% in normal blood glucose group (p=0.004). The higher the admission blood glucose level there is more incidence of contrast induced nephropathy. Multivariate analysis of factors associated with CIN shows that patients with high blood glucose (>7.8 mmol/l) and > 150 ml of contrast exposure are independent predictors of contrast induced nephropathy. The patients subjected to PCI having high blood glucose were at 6 times higher risk of developing CIN than normal blood glucose and use of contrast >150 ml were more than 2 times higher risk of developing CIN. Conclusion: Patients with high blood sugar on admission of ACS patients have more chance of developing CIN after PCI. Cardiovasc. j. 2017; 9(2): 106-115